A Pilot Study of Associations Between the Occurrence of Palpitations and Cytokine Gene Variations in Women Prior to Breast Cancer Surgery. Issue 2 (April 2023) - Sheng, Ying; Carpenter, Janet S.; Smith, Brenda J.; Paul, Steven M.; Melisko, Michelle; Moslehi, Javid; Levine, Jon D.; Conley, Yvette P.; Kober, Kord M.; Miaskowski, Christine
Objectives: Palpitations are common and have a negative impact on women's quality of life. While evidence suggests that inflammatory mechanisms may play a role in the development of palpitations, no studies have evaluated for this association in patients with breast cancer who report palpitations prior to surgery. The purpose of this pilot study was to evaluate for associations between the occurrence of palpitations and single nucleotide polymorphisms (SNPs) in genes for pro- and anti-inflammatory cytokines, their receptors, and transcriptional regulators. Methods: Patients were recruited prior to surgery and completed a self-report questionnaire on the occurrence of palpitations. Genotyping of SNPs in cytokine genes was performed using a custom array. Multiple logistic regression analyses were done to identify associations between the occurrence of palpitations and SNPs in fifteen candidate genes. Results: Of the 82 SNPs evaluated in the bivariate analyses, eleven SNPs in 6 genes were associated with the occurrence of palpitations. After controlling for functional status, the occurrence of back pain, and self-reported and genomic estimates of race/ethnicity, 3 SNPs in 3 different genes (i.e., interleukin (IL) 1-beta (IL1B) rs1143643, IL10 rs3024505, IL13 rs1295686) were associated with the occurrence of palpitations prior to surgery (all p ≤ .038). Conclusions: While these preliminary findings warrant replication, they suggest that inflammatory mechanisms may contribute to the subjective sensation of palpitations in women prior to breast cancer surgery.